SCM Produk Pertanian Berbasis IT - Budi Sulistyo (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Conceptually, Supply Chain Management (SCM) includes all value-adding activitiesfrom the extraction of raw materials through the transformation process and through deliveryto the end user.Supply Chain Management is one of the principal areas which focusing to increasecompetitive advantage and shareholder value and reduce cost production and distribution.The SCM for agriculture product distribution in Indonesia is a chain of process thatfacilitates business activity between trading partners, from the purchase of raw goods andsupporting products for farming to the delivered process of the agriculture product to themarket. The production and distribution of agriculture products in Indonesia largely possessa number of weaknesses and inefficiencies such as unplanned and poorly-managedproduction, as well as lengthy distribution chain and unstable price. In this paper, we proposea model of implemented SCM Network for Agriculture Product Distribution in Indonesia tocreate a better communication and distribution network among the players based onInformation Technology.Keywords: supply chain management, agriculture product, distribution, informationtechnology